Memanfaatkan Peluang Bisnis di Era Pandemi Melalui Pelatihan Kerajinan Tangan - Putry Julia; Hambali; Dian Aswita; Muhammad Isa; Rahmani; Faisal Anwar (Yayasan Literasi Sains Indonesia, 2022)
Covid-19 pandemic which has been going on for approximately the last two years and has had a major impact on the Indonesian people and economy. Indonesia's economic activity is getting weaker and lowering people's purchasing power. One of the prevention strategies implemented by the government is by limiting community mobility through work from home and also study from home for the community. Since the enactment of this policy, people have more free time at home. Therefore, this PKM activity aims to introduce business opportunities that can be utilized by the community. This free handicraft training hopes that the participants will maximize the training to make handicrafts from hemp/jute rope and earn additional income during the pandemic. The target of this activity is the community in Lamteuba Droe Village, Seulimum, Aceh Besar District. Based on the results of the work made by the participants, this PKM activity can be said to be successful in the first experiment because they can create and produce their work well in each group. The handicrafts made have also met the expectations of the PKM team and can be said to be worthy of sale.